The TINGKAT KEPESERTAAN KELUARGA BERENCANA TERHADAP PEMAKAIAN KONTRASEPSI DI KECAMATAN LEUWISADENG 2022 - Febriyanti; Dewi Purnamawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2023)
The primary indicator of the success of Family Planning (FP) will be evident from the number of contraceptive users among women of reproductive age (WRA). This study aims to evaluate the participation rate in FP and the utilization of contraceptives in Leuwisadeng District in the year 2022. Method: A descriptive research design with a quantitative approach was employed. The study population consisted of WRA in the Leuwisadeng District, with the research sample drawn from the population of FP participants. Data were collected from family registration reports through the New SIGA application and analyzed through univariate analysis by calculating percentages, which were then presented in tabular form. Results: FP participation rate: The total number of WRA in 2022 was 13,375 individuals. Out of these, 9,785 individuals (73%) were FP participants, while 3,593 individuals (27%) were non-participants. The most commonly used contraceptive method was injectable contraceptives, with a total of 6,158 individuals (62% of the total FP participants). Oral contraceptive pills were used by 2,281 individuals (23%), intrauterine devices (IUDs) by 130 individuals (1.3%), the Woman Operation Methode/Tubectomy by 96 individuals (1%), implants by 976 individuals (10%), condoms by 110 individuals (1.1%), and Vasectomy by 24 individuals (0.2%). Conclusion: The FP program in Leuwisadeng District in 2022 has achieved a reasonably good level of participation, with 73% of the total WRA being FP participants. However, there are still a significant number of WRA who have not yet participated in FP, and injectable contraceptives are the most commonly used method. Recommendation: Cross-sectoral collaboration is needed to promote family planning and enhance participation in the FP program.